Everything You Know about Indians Is Wrong - Smith, Paul Chaat (Book collections on Project MUSE., 2009)
In this sweeping work of memoir and commentary, leading cultural critic Paul Chaat Smith illustrates with dry wit and brutal honesty the contradictions of life in "the Indian business."Raised in suburban Maryland and Oklahoma, Smith dove head first into the political radicalism of the 1970s, working with the American Indian Movement until it dissolved into dysfunction and infighting. Afterward he lived in New York, the city of choice for political exiles, and eventually arrived in Washington, D.C., at the newly minted National Museum of the American Indian ("a bad idea whose time has come") as a curator.